HBR Classics Boxed Set (16 Books) - Review, Harvard Business. (Harvard business review classics., 2017)
The classic Harvard Business Review articles every manager and aspiring leader should read--and share with their teams--from such bestselling Harvard Business Review authors as Peter Drucker, Clayton Christensen, John Kotter, Daniel Goleman, Jim Collins, Gary Hamel, W. Chan Kim, Renee Mauborgne, and many more. Each compact book represents the most important ideas on management, leadership, and life. Build your professional library and advance your career with these 16 timeless business classics. The HBR Classics Boxed Set includes: Peter Drucker's bestselling "Managing Oneself," "What Makes an Effective Executive," and "The Theory of the Business"; Clayton Christensen's inspiring "How Will You Measure Your Life?"; Daniel Goleman's articles on emotional intelligence--"Leadership That Gets Results" and "What Makes a Leader?"; author of Good to Great Jim Collins's "Turning Goals into Results"; W. Chan Kim and Renee Mauborgne's "Blue Ocean Leadership" and "Red Ocean Traps"; John Kotter's "Managing Your Boss"; Jon Katzenbach and Douglas Smith's "The Discipline of Teams"; Gary Hamel and C.K. Prahalad's "Strategic Intent"; William A. Sahlman's "How to Write a Great Business Plan"; Chris Argyris's "Teaching Smart People How to Learn"; Theodore Levitt's "Marketing Myopia"; Joseph B. Pine's "Do You Want to Keep Your Customers Forever?". The Harvard Business Review Classics series offers you the opportunity to make seminal Harvard Business Review articles a part of your permanent management library. Each highly readable volume contains a groundbreaking idea that continues to shape best practices and inspire countless managers around the world--and will have a direct impact on you today and for years to come.